2016
DOI: 10.1371/journal.pone.0149115
|View full text |Cite
|
Sign up to set email alerts
|

Combining Amplitude Spectrum Area with Previous Shock Information Using Neural Networks Improves Prediction Performance of Defibrillation Outcome for Subsequent Shocks in Out-Of-Hospital Cardiac Arrest Patients

Abstract: ObjectiveQuantitative ventricular fibrillation (VF) waveform analysis is a potentially powerful tool to optimize defibrillation. However, whether combining VF features with additional attributes that related to the previous shock could enhance the prediction performance for subsequent shocks is still uncertain.MethodsA total of 528 defibrillation shocks from 199 patients experienced out-of-hospital cardiac arrest were analyzed in this study. VF waveform was quantified using amplitude spectrum area (AMSA) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Research has suggested that prior rhythm is associated with subsequent likelihood of return of spontaneous circulation following shock, and that this information may improve prediction when combined with waveform measures calculated during CPR-free epochs. 16,17 However little is known about whether ROR from prior shock would improve prediction when combined with waveform measures calculated during CPR. We observed that Prior ROR was associated with the response to a subsequent shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that prior rhythm is associated with subsequent likelihood of return of spontaneous circulation following shock, and that this information may improve prediction when combined with waveform measures calculated during CPR-free epochs. 16,17 However little is known about whether ROR from prior shock would improve prediction when combined with waveform measures calculated during CPR. We observed that Prior ROR was associated with the response to a subsequent shock.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that prior rhythm and perfusion state are associated with subsequent likelihood of return of spontaneous circulation following shock, 16 and that this information in combination with waveform measures may improve prediction of shock success. 17 However, this relationship has not been tested during CPR, challenging real-world implementation of such a strategy. If a combination algorithm could more accurately predict shock success during CPR, then shock delivery might be timed based on a real-time prognostic likelihood calculated during continuous CPR.…”
Section: Introductionmentioning
confidence: 99%
“…FuzzEn showed a decrease in BER of 3-5 points with respect to PPA, MdS and/or AMSA. Most likely, shock outcome prediction could be improved by incorporating additional information, such as the relative changes in the predictors between consecutive shocks [59], or other clinical variables, such as end tidal CO2 levels [58].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence updates restricted the search to January 2008 to January 2020 and identified one large RCT conducted in 2013 45 and 20 observational studies. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 In addition, there is an ongoing multicentre RCT of real-time amplitude spectrum area to guide defibrillation (NCT03237910). Although the VF waveform analyses and outcomes studied were highly heterogeneous, given the amount of data available, an updated SysRev was suggested.…”
Section: Defibrillation Strategies For Ventricular Fibrillation or Pumentioning
confidence: 99%